Evaluating Heavy Metal Pollution In The Batang Masumai River Water, Merangin District, Jambi Province Using The Heavy Metal Pollution Index/HPI - Astuti, Syurmi; Irsan Saleh, Muhammad; Arita, Susila; Legiran, Legiran (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
River water pollution has become a major concern, particularly in regions where human activities occur without proper regulation. This study investigates heavy metal contamination in the Batang Masumai River, Merangin Regency, Jambi Province, where local residents conduct mining near the riverbanks. Water samples were taken from upstream, midstream and downstream, then analyzed using Atomic Absorption Spectrometry (AAS) to detect concentrations of seven metals: mercury (Hg), cadmium (Cd), nickel (Ni), iron (Fe), copper (Cu), manganese (Mn), and lead (Pb). Heavy metals  are among the most dangerous pollutants due to their toxicity, persistence, and impact on human health Pollution levels were evaluated through the Heavy Metal Pollution Index (HPI) and compared with SNI 6242:2015 and WHO 2022 standards. The results showed that cadmium, nickel, iron, and mercury exceeded allowable limits. The HPI results reflect a serious level of water pollution. Based on the 2015 SNI standard, the HPI scores are 214.45 for downstream, a striking 57893.41 for midstream, and 120.61 for upstream. Using the the WHO 2022 criteria, the values are 486.03 (downstream), 4.186.55 (midstream) and 267.83 (upstream). Except for the upstream based on SNI 6242:2015, all areas show high contamination levels (HPI ≥ 200), highlighting a concerning environmental issue. Mercury and cadmium, known for their high toxicity and bioaccumulation potential, were the most concerning. These findings underscore the urgent need for remediation efforts, continuous environmental monitoring, and increased public awareness to protect aquatic ecosystems and ensure the safety of water resources for surrounding communities.